Infrastructure and cluster development: A case study of handloom weavers in Ethiopia - Ayele, Gezahegn; Chamberlin, Jordan; Moorman, Lisa; Wamisho, Kassu; Zhang, Xiaobo (International Food Policy Research Institute, 2009)
This paper evaluates the impacts of access to infrastructure on development of handloom weaving clusters in Ethiopia based on a survey collected in both urban and rural areas. Geographical clustering enables entrepreneurs with limited capital to enter the business through shared workspaces and greater specialization of labor. In towns with electricity access, producers work longer hours by sharing workspaces with electric lights at lower rental cost, resulting in higher labor productivity.